Híbridos de ZnO auto-organizado na forma de estrelas e nanopartículas metálicas (Ag, Au) : síntese controlada e avaliação fotocatalítica e antibacteriana - Andrade, George Ricardo Santana (2016)
Zinc oxide (ZnO) microparticles with a star-shaped morphology have been synthesized by a novel and simple room-temperature method and decorated with gold (GNP) and silver (SNP) nanoparticles for enhanced photocatalysis and bactericide applications. The presence of thiourea during the precipitation of ZnO in alkaline conditions allowed the control of morphological features (e.g. average size and shape) and the surface functionalization with thiocyanate ions (SCN-). TEM images of the sample prepared at pH 12 suggest that the particles grow according to the oriented attachment mechanism. The emission spectra of these particles showed an interesting feature: the emission band position can be tunable by changing the excitation wavelength. SNPs and GNPs were prepared onto ZnO surface by a photoreduction method and it was found that their sizes can be easily controlled by changing the ZnO/AgNO3 or ZnO/HAuCl4 ratios. The presence of SCN- on the semiconductor surface prevents uncontrollable growth of Ag nanoparticles into different morphologies and high degrees of polydispersity. XRD, SEM, TEM, FTIR, UV-vis-NIR and PL were employed for characterizing the structure, morphology and optical properties of asobtained pure and hybrid nanostructures. Finally, the hybrid ZnO/Ag particles show plasmon-enhanced performance for applications in photocatalysis and antibacterial activity than the pure ZnO counterpart. In this work, it was studied the photodegradation of an aqueous methylene blue solution under UV-A irradiation and antibacterial activity toward 4 bacterial strains, including Gram-positive bacteria Staphylococcus aureus (ATCC 43300, ATCC 25923 and ATCC 33591) and Gram-negative bacteria Pseudomonas aeruginosa (ATCC 27853).